Evaluation of Hardwoods of Andaman and Nicobar Islands for Kraft Pulps for Wrapping, Writing and Printing Papers - Mahajan, Sushma; Raj, A. K.; Singh, S. P.; Dhoundiyal, S. N.; Sharma, Y. K.; Singh, S. V. (Indian Forester, 1985)
The present paper gives a comparative account of basic density and kraft pulping characteristics of fourteen species of Barataung area and eighteen species of Middle Andman area of Andaman&Nicobar Islands. The properties of kraft pulps of individual species have also been evaluated. It has been found that the basic density varied widely with species in both areas. In Barstaung area the variation was from 0.302 to 0.847 g/cm2, whereas for Middle Andaman gives area it was in between 0.261 to 0.728 g/cm2. Laboratory experiments on kraft pulping of individual species have shown that most of them gave screened pulp in the range of 40-45% yield, the only exception being Mitraeyna retundifolia of Barataung area and Knema sp of Middle Andaman area which gave pulp yield below 40%. The physical strength properties of unbleached kraft pulps of all the species were found to be adequate for wrapping grade paper. Pilot plant trials have shown that the mixed species of both areas could be pulped wlth 18% active alkali (as Na2O) to produce unbleached kraft pulps of about 45% of yield. The paper made from these unbleached kraft pulps on pilot paper machine was of satisfactory strength for use as wrapping paper. It was further established that these pulps could be bleached to 75 brightness by conventional C/E/H/H/ sequence to produce writing and printing paper.